Estudo das propriedades fotofísicas de molibdatos de estrôncio dopados com európio (III) - Tanaka, Marcos Takashi Santos (Universidade Federal de São Carlos, 2011)
Study of the photophysical properties of strontium molybdates doped with Europium (III). In this project the strontium molybdates doped with europium were characterized using various techniques like X-ray diffraction, infrared and Raman spectroscopy, and also the study of the behavior of luminescent inorganic materials. The materials were prepared by complex polymerization method. Analyses of X-ray diffraction powder were performed to determine the achievement of the desired phase in the oxides. The doped materials at different europium concentrations were heated to different temperatures. The emission spectra of europium were achieved exciting the synthesized samples at specific wavelengths. These spectra were analyzed and correlated with the thermal treatment temperature, as well as the concentration of Eu3+. The lifetimes of the europium 5D0→7F2 emission for all samples were evaluated. The emission spectra of the pure strontium molybdate matrix were also obtained and analyzed. These studies permitted to determine the maximum concentration of the soluble europium in the crystal lattice of strontium molybdate framework most favorable for the emission of europium.
Keywords: Química; Luminescência; Terras raras; CIENCIAS EXATAS E DA TERRA::QUIMICA